Analysis of speech and hearing cases seen in camps:- a report - Venkatesh Aithal (Journal of All India Institute of Speech and Hearing, 1970)
The prevalence and incidence of communication disorders involving speech, language and hearing needs to be carefully studied. Estimates of prevalence and incidence of these disorders in the general population are few, and probably needs more careful study.